Selective positioning of organic dyes in a mesoporous inorganic oxide film - Lee, Kyungtae; Park, Se Woong; Ko, Min Jae; Kim, Kyungkon; Park, Nam-Gyu (NATURE PUBLISHING GROUP, 2009)
Although sequential adsorption of dyes in a single TiO2 electrode is ideal to extend the range of light absorption in dye-sensitized solar cells, high-temperature processing has so far limited its application. We report a method for selective positioning of organic dye molecules with different absorption ranges in a mesoporous TiO2 film by mimicking the concept of the stationary phase and the mobile phase in column chromatography, where polystyrene-filled mesoporous TiO2 film is explored for use as a stationary phase and a Bronsted-base-containing polymer solution is developed for use as a mobile phase for selective desorption of the adsorbed dye. By controlling the desorption and adsorption depth, yellow, red and green dyes were vertically aligned within a TiO2 film, which is confirmed by an electron probe micro-analyser. The external quantum efficiency (EQE) spectrum from a solar cell with three selectively positioned dyes reveals the EQE characteristics of each single-dye cell.
Keywords: SENSITIZED SOLAR-CELLS; HYBRID MULTILAYER; IMPEDANCE SPECTROSCOPY; ELECTRICAL-IMPEDANCE; NANOPOROUS MATERIAL; EFFICIENCY; TRANSPORT; RECOMBINATION; ELECTROLYTE; FABRICATION